(untitled) (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of this study is to investigate aspects of digital law in Ukraine and other countries of the world in the context of the right to be forgotten. [Methodology/Approach/Design] To achieve the objective, induction, deduction, and comparative analysis were used, both the proximate topics and aspects of the legal framework of different countries together with the legal information provided by online services were considered. [Findings] The study identified the main features of the right to be forgotten in different countries, the impact of the European Union Court of Justice and European Court of Human Rights on it and the little-studied intricacies of the legal aspect of this mechanism. [Practical Implications] This paper can be of interest both as introductory material and as a basis for further study because there is a growing human need to be able to control personal data in the face of the expanding phenomenon of globalization and digitalization.